Using Water Balance to Analyze Water Availability for Communities ( A Case Study in Some Areas of Bengawan Solo Watershed) - Alif Noor Anna; Kuswaji Dwi Priyono; Suharjo Suharjo; Yuli Priyana (Forum Geografi, 2016)
This study aimed: (a) to determine the general water balance at the Upstream and Midstream of Bengawan Solo Watershed by using Thornthwaite-Mather model, and (b) to determine the fulfillment of domestic water demand in the Upstream and Midstream of Bengawan Solo Watershed. Prevailing climate change has affected the condition of water source in Upstream and Midstream of Bengawan Solo Watershed. One of the impacts was extreme fluctuation of meteorological water availability that might cause flood and drought. Survey was selected as the research method while descriptive quantitative method was used for data analysis. The findings indicated the difference between precipitation and corrected evapotranspiration (P-EP) at the Upstream and Midstream of Bengawan Solo Watershed was between (-11.19 mm) to (78.56 mm). The highest value was obtained by Bambang Sub-watershed and the lowest was Wiroko Temon Sub-watershed. Positive value indicated the water surplus while negative value indicated water deficit. Domestic water demand for local communities was in the range of 50,782,500 liters to 131,690,700 liters, and the level of water availability varied, namely fulfilled and unfulfilled.